How does Top Management Team (TMT) Characteristics Influence a Firm’s Degree of Internationalization? - an Empirical Research by the Case of China - Su, Na (2020)
With the deepening of internationalization, the foreign direct investment activities of multinational enterprises in emerging markets have attracted enhanced attention. However, emerging economies differ from developed countries in many aspects. Therefore, whether the existing FDI theory can be applied to emerging multinational corporations remains to be verified. This dissertation analyzes a sample of 825 listed multinational companies in China’s manufacturing industry and finds that TMT’s personal characteristics such as age, education level and international experience will affect the degree of internationalization of multinational enterprises in emerging economies. Therefore, this dissertation provides a perspective of managers to explain the internationalization of multinational companies in emerging markets.